2023
DOI: 10.3390/toxics11020160
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Ameliorates Diquat-Induced Testicular Toxicity via Reducing Oxidative Stress, Inhibiting Apoptosis, and Maintaining the Integrity of Blood-Testis Barrier in Mice

Abstract: Diquat is a fast, potent, and widely used bipyridine herbicide in agriculture and it induces oxidative stress in several animal models. However, its genotoxic effects on the male reproductive system remain unclear. Melatonin is an effective free-radical scavenger, which has antioxidant and anti-apoptotic properties and can protect the testes against oxidative damage. This study aimed to investigate the therapeutic effects of melatonin on diquat-induced testicular injury in mice. The results showed melatonin tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Feng et al showed that naringin reduced cerebral ischemia-reperfusion damage in rats through mitophagy activation. In their study, naringin could suppress apoptosis and inhibit the translocation of Parkin to the mitochondria in the ischemia-reperfused rat brains (12). Conversely, excessive mitophagy induces apoptosis in cancerous cells, in particular (39).…”
Section: Khorsandi Et Almentioning
confidence: 92%
See 1 more Smart Citation
“…Feng et al showed that naringin reduced cerebral ischemia-reperfusion damage in rats through mitophagy activation. In their study, naringin could suppress apoptosis and inhibit the translocation of Parkin to the mitochondria in the ischemia-reperfused rat brains (12). Conversely, excessive mitophagy induces apoptosis in cancerous cells, in particular (39).…”
Section: Khorsandi Et Almentioning
confidence: 92%
“…BPA induces Sertoli cell death in rodents by causing mitochondrial dysfunction and excessive ROS generation (4). Feng et al showed that BPA induces cell cycle arrest and apoptosis by preventing ROS levels in the porcine Sertoli cells (12). It is, therefore, necessary to find preventive and therapeutic agents to address BPA-induced reproductive toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In cases of large ingestions, patients can develop symptoms of acute renal failure ( Tanen et al, 1999 ; Fortenberry et al, 2016 ; Huang et al, 2021 ). Additionally, DQ can exert toxic effects on other organ systems, including the liver ( Burk Rf Fau - Lawrence et al, 1980 ), lungs ( Manabe J Fau - Ogata et al, 1986 ), heart, central nervous system ( Lu et al, 2022 ), digestive tract, airways ( Tanen et al, 1999 ), skin, and reproductive system ( Guangcai et al, 2022 ; Zhou and Lu, 2022 ; Yang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%